A method for preparing high-strength cosmetic glass container

By adding cerium trifluoride to the glass matrix of cosmetic glass containers, the gradient distribution of elements is promoted, and the limitations of traditional glass containers in terms of chemical corrosion resistance, impact strength and environmental protection recycling are solved, and higher impact resistance, wear resistance and dimensional stability are achieved.

CN119080397BActive Publication Date: 2025-04-15GUANGDONG YIFANG PACKAGING PROD CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411188351.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-04-15
Estimated Expiration
2044-08-28

AI Technical Summary

Technical Problem

Traditional cosmetic glass containers have limitations in their chemical corrosion resistance, impact resistance and environmental protection recycling, especially the binding force of neodymium and dysprosium elements to the glass matrix is ​​limited.

Method used

By adding cerium trifluoride as an intermediate layer to the glass matrix, the gradient distribution of elements is promoted, the binding force between the neodymium fluoride/dysprosium fluoride layer and the glass matrix is ​​enhanced, and the cerium element is quickly penetrated into the glass matrix through high-temperature heat treatment, refines the grains, and improves the density and wear resistance of the glass container.

Benefits of technology

The bonding force between the neodymium fluoride/dysprosium fluoride layer and the glass matrix is ​​improved, the impact resistance, wear resistance and dimensional stability of the glass container are enhanced, and the segregation phenomenon is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005014237160000061
    Figure BDA0005014237160000061
  • Figure BDA0005014237160000071
    Figure BDA0005014237160000071
Patent Text Reader

Abstract

The present invention relates to a method for preparing a high-strength cosmetic glass container, and belongs to the technical field of glass containers. A method for preparing a high-strength cosmetic glass container comprises the following steps: grinding and mixing quartz sand, soda ash, aluminum oxide, borax, barium carbonate, calcium oxide, magnesium oxide and cerium trifluoride raw materials, heating and melting and continuously stirring, adding neodymium fluoride and dysprosium fluoride, cooling and melting to obtain glass liquid; injecting the glass liquid into a preheated copper mold for molding to obtain a preform; heat-treating the preform to obtain a high-strength cosmetic glass container. The present invention uses cerium trifluoride as an intermediate layer support and promotes the gradient distribution of elements, thereby enhancing the bonding force between the neodymium fluoride / dysprosium fluoride layer and the glass matrix, and the cerium element quickly penetrates under heat treatment to refine the grains. The refinement of the grains and uniformity improve the density and mechanical properties of the glass container; the glass container prepared by the present invention has the characteristics of excellent impact resistance and Mohs hardness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass containers and relates to a method for preparing a high-strength cosmetic glass container. Background Art

[0002] With the rapid development of the cosmetics industry, consumers are not only looking for beauty and portability in cosmetic packaging, but also have higher requirements for the durability, safety and environmental performance of containers. Although traditional cosmetic packaging materials, such as plastic and ordinary glass, meet basic packaging needs to a certain extent, they have certain limitations in terms of chemical corrosion resistance, impact strength and environmental recycling.

[0003] There is a significant difference in melting point between the glass matrix and NdF and DyF, and the large difference in thermal expansion coefficient and atomic radius between the two also limits their diffusion capacity. These factors work together to limit the bonding strength between NdF and DyF and the glass matrix. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a high-strength cosmetic glass container. In the present invention, cerium trifluoride is added as an intermediate layer to support and promote element gradient distribution, enhance the bonding strength between the neodymium fluoride / dysprosium fluoride layer and the glass matrix, and the cerium element quickly penetrates into the glass matrix at high temperature to refine the grains, thereby improving the density, uniformity and wear resistance of the glass container and reducing segregation.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a high-strength cosmetic glass container, the method comprising the following steps:

[0007] 1) grinding and mixing quartz sand, soda ash, aluminum oxide, borax, barium carbonate, calcium oxide, magnesium oxide and cerium trifluoride raw materials to obtain a premix;

[0008] 2) heating and melting the premix while continuously stirring to obtain a base liquid;

[0009] 3) adding neodymium fluoride and dysprosium fluoride to the base liquid, cooling and melting to obtain glass liquid;

[0010] 4) injecting the glass liquid into the preheated copper mold to form a preform;

[0011] 5) The preform is heat-treated to obtain a high-strength cosmetic glass container.

[0012] As a preferred technical solution of the present invention, the addition of cerium trifluoride can interrupt the continuous network of silicon-oxygen tetrahedrons to form smaller aggregates, increase the rigidity of the glass network, limit the slip mechanism inside the glass, and improve the tensile strength and hardness. Since cerium trifluoride can effectively reduce the volume expansion or contraction of the glass material when the temperature changes, improve its dimensional stability and thermal shock resistance, it can quickly eliminate internal stress under high heat treatment, and then eliminate internal stress by cooling. High-temperature heat treatment induces the precipitation of fluoride nanocrystals.

[0013] As a preferred technical solution of the present invention, in step 1), the grinding is grinding to a particle size of 0.6-0.8 mm.

[0014] As a preferred technical solution of the present invention, in step 2), the heating melting is melting at a temperature of 1600-1700° C. for 35-45 minutes.

[0015] As a preferred technical solution of the present invention, in step 3), the temperature reduction melting is melting at a temperature of 1550-1640° C. for 15-20 minutes.

[0016] As a preferred technical solution of the present invention, in step 4), the preheating temperature of the copper mold is 300°C.

[0017] As a preferred technical solution of the present invention, in step 5), the heat treatment is annealing at a temperature of 480-520°C for 5-6h. Due to the addition of cerium trifluoride, the thermal stability and the bonding force between the elements are increased, so that at the heat treatment temperature of 480-520°C, the elements are quickly and evenly distributed, and the internal stress can be quickly eliminated. The temperature is air-cooled to 420-460°C for annealing for 1.0-1.5h to eliminate the internal stress, and the heat treatment is performed at a temperature of 630-650°C for 2-3h to induce the precipitation of fluoride nanocrystals.

[0018] The invention discloses a high-strength cosmetic glass container, which comprises the following components in parts by weight: 100-120 parts of quartz sand, 20-25 parts of soda ash, 10-12 parts of aluminum oxide, 6-8 parts of borax, 2.6-3.5 parts of barium carbonate, 12-16 parts of calcium oxide, 4-6 parts of magnesium oxide, 2.0-2.5 parts of cerium trifluoride, 1.5-2.0 parts of neodymium fluoride and 0.5-0.6 parts of dysprosium fluoride.

[0019] Beneficial effects of the present invention:

[0020] The present invention introduces cerium trifluoride to form a solid solution between a glass matrix and neodymium fluoride / dysprosium fluoride, and forms a compound with multiple stable components on its surface. Cerium trifluoride is used as an intermediate layer to provide support force, so that elements in each layer are distributed in a gradient, thereby improving the bonding force between the neodymium fluoride / dysprosium fluoride layer and the glass matrix. The cerium element penetrates into the glass matrix through thermal diffusion under a relatively high melting environment and acts as an intermediate layer. The relatively high melting temperature is conducive to the rapid penetration of the cerium element. The relatively low melting temperature in the latter stage is conducive to refining the grains, improving the density and uniformity of the glass container, improving the wear resistance of the glass container, and reducing the segregation phenomenon. DETAILED DESCRIPTION

[0021] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0022] Example 1

[0023] The high-strength cosmetic glass container comprises the following components in parts by weight: 100 parts of quartz sand, 20 parts of soda ash, 10 parts of aluminum oxide, 6 parts of borax, 2.6 parts of barium carbonate, 12 parts of calcium oxide, 4 parts of magnesium oxide, 2.0 parts of cerium trifluoride, 1.5 parts of neodymium fluoride and 0.5 parts of dysprosium fluoride.

[0024] A method for preparing a high-strength cosmetic glass container, the method comprising the following steps:

[0025] 1) grinding quartz sand, soda ash, aluminum oxide, borax, barium carbonate, calcium oxide, magnesium oxide and cerium trifluoride raw materials to a particle size of 0.6 mm to obtain a premix;

[0026] 2) heating the premix to 1600° C. and melting for 35 min with continuous stirring to obtain a base liquid;

[0027] 3) After adding neodymium fluoride and dysprosium fluoride to the base liquid, the temperature is lowered to 1550° C. and melted for 15 minutes to obtain glass liquid;

[0028] 4) injecting the glass liquid into the preheated copper mold to form a preformed product; the preheating temperature of the copper mold is 300° C.;

[0029] 5) heat-treating the preform to obtain a high-strength cosmetic glass container; wherein the heat treatment is annealing at 480° C. for 5 h, air cooling to 420° C. for 1.0 h, and heat-treating at 630° C. for 2 h.

[0030] Example 2

[0031] The high-strength cosmetic glass container comprises the following components in parts by weight: 108 parts of quartz sand, 22 parts of soda ash, 10.5 parts of aluminum oxide, 6.8 parts of borax, 2.8 parts of barium carbonate, 13 parts of calcium oxide, 4.8 parts of magnesium oxide, 2.2 parts of cerium trifluoride, 1.7 parts of neodymium fluoride and 0.55 parts of dysprosium fluoride.

[0032] A method for preparing a high-strength cosmetic glass container, the method comprising the following steps:

[0033] 1) grinding quartz sand, soda ash, aluminum oxide, borax, barium carbonate, calcium oxide, magnesium oxide and cerium trifluoride raw materials to a particle size of 0.7 mm to obtain a premix;

[0034] 2) heating the premix to 1630° C. and melting for 38 min with continuous stirring to obtain a base liquid;

[0035] 3) After adding neodymium fluoride and dysprosium fluoride to the base liquid, the temperature is lowered to 1580°C and melted for 17 minutes to obtain glass liquid;

[0036] 4) injecting the glass liquid into the preheated copper mold to form a preformed product; the preheating temperature of the copper mold is 300° C.;

[0037] 5) heat-treating the preform to obtain a high-strength cosmetic glass container; wherein the heat treatment comprises annealing at 490° C. for 5.5 h, air cooling to 430° C. for 1.2 h, and heat treatment at 630° C. for 2.5 h.

[0038] Example 3

[0039] The high-strength cosmetic glass container comprises the following components in parts by weight: 115 parts of quartz sand, 23 parts of soda ash, 11.5 parts of aluminum oxide, 7.2 parts of borax, 3.2 parts of barium carbonate, 14 parts of calcium oxide, 5.2 parts of magnesium oxide, 2.5 parts of cerium trifluoride, 1.8 parts of neodymium fluoride and 0.55 parts of dysprosium fluoride.

[0040] A method for preparing a high-strength cosmetic glass container, the method comprising the following steps:

[0041] 1) grinding quartz sand, soda ash, aluminum oxide, borax, barium carbonate, calcium oxide, magnesium oxide and cerium trifluoride raw materials to a particle size of 0.7 mm to obtain a premix;

[0042] 2) heating the premix to 1660° C. and melting for 42 min with continuous stirring to obtain a base liquid;

[0043] 3) After adding neodymium fluoride and dysprosium fluoride to the base liquid, the temperature is lowered to 1610° C. and melted for 18 minutes to obtain glass liquid;

[0044] 4) injecting the glass liquid into the preheated copper mold to form a preformed product; the preheating temperature of the copper mold is 300° C.;

[0045] 5) heat-treating the preform to obtain a high-strength cosmetic glass container; wherein the heat treatment is annealing at 510° C. for 5.5 h, air cooling to 445° C. for 1.3 h, and heat treatment at 640° C. for 2.5 h.

[0046] Example 4

[0047] The high-strength cosmetic glass container comprises the following components in parts by weight: 120 parts of quartz sand, 25 parts of soda ash, 12 parts of aluminum oxide, 8 parts of borax, 3.5 parts of barium carbonate, 16 parts of calcium oxide, 6 parts of magnesium oxide, 2.5 parts of cerium trifluoride, 2.0 parts of neodymium fluoride and 0.6 parts of dysprosium fluoride.

[0048] A method for preparing a high-strength cosmetic glass container, the preparation method comprising the following steps:

[0049] 1) grinding quartz sand, soda ash, aluminum oxide, borax, barium carbonate, calcium oxide, magnesium oxide and cerium trifluoride raw materials to a particle size of 0.8 mm to obtain a premix;

[0050] 2) heating the premix to 1700° C. and melting for 45 min with continuous stirring to obtain a base liquid;

[0051] 3) After adding neodymium fluoride and dysprosium fluoride to the base liquid, the temperature is lowered to 1640° C. and melted for 20 minutes to obtain glass liquid;

[0052] 4) injecting the glass liquid into the preheated copper mold to form a preformed product; the preheating temperature of the copper mold is 300° C.;

[0053] 5) heat-treating the preform to obtain a high-strength cosmetic glass container; wherein the heat treatment is annealing at 520° C. for 6 hours, air cooling to 460° C. for annealing for 1.5 hours, and heat treatment at 650° C. for 3 hours.

[0054] Comparative Example 1

[0055] Compared with Example 3, Comparative Example 1 is different in that cerium trifluoride is not added, and the other components, preparation steps and parameters are the same.

[0056] Comparative Example 2

[0057] Compared with Example 3, Comparative Example 2 is different in that the premix, neodymium fluoride and dysprosium fluoride are added after mixing in step 2);

[0058] Step 2): after mixing the premix, neodymium fluoride and dysprosium fluoride, heating to 1660° C. and melting for 42 minutes with continuous stirring to obtain a base liquid;

[0059] Step 3): the base liquid is cooled to 1610° C. and melted for 18 minutes to obtain glass liquid;

[0060] The remaining components, preparation steps and parameters were the same.

[0061] Comparative Example 3

[0062] Compared with Example 3, the difference of Comparative Example 3 is that the heat treatment is annealing at a temperature of 510° C. for 6.8 hours, and the other components, preparation steps and parameters are the same.

[0063] Comparative Example 4

[0064] Compared with Example 3, the difference in Comparative Example 4 is that the heat treatment is annealing at 445° C. for 6.8 h, and the other components, preparation steps and parameters are the same.

[0065] The glass containers prepared in Examples 1-4 and Comparative Examples 1-4 were tested as follows, and the test results are shown in Table 1.

[0066] (I) The glass container is made into a 4 mm thick flat glass sample, and a 1040 g steel ball is used to perform a drop ball impact test on each flat glass sample using a tempered glass component drop ball impact tester to detect the starting height of the steel ball from the flat glass sample when each flat glass sample is broken by the impact of the steel ball.

[0067] (ii) Use a Mohs hardness tester to test the Mohs hardness of the glass sample.

[0068] Table 1

[0069]

[0070]

[0071] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-4, the glass containers prepared by the present invention have excellent impact resistance and Mohs hardness. By comparing Examples 1-4 and Comparative Examples 1-4 in combination with Table 1, it can be seen that Comparative Example 1 lacks cerium trifluoride, cerium trifluoride cannot be used as an intermediate layer, and cannot form a solid solution between the glass matrix and neodymium fluoride / dysprosium fluoride, and the binding force of its internal structure leads to a decrease in structural stability; Comparative Example 2 cerium trifluoride, neodymium fluoride and dysprosium fluoride are added at the same time, and part of the neodymium and dysprosium elements are first combined with the glass matrix, without cerium as an intermediate bridge, lacking cerium trifluoride to provide support, and the neodymium and dysprosium elements cannot be well combined with the glass matrix, resulting in a decrease in impact resistance and Mohs hardness; Comparative Examples 3-4 have different heat treatment methods, and the cerium element cannot penetrate quickly, the grains are rough and affect their dispersibility, resulting in a decrease in its mechanical properties.

[0072] In summary, the present invention introduces cerium trifluoride to form a solid solution between the glass matrix and neodymium fluoride / dysprosium fluoride, and forms a compound with multiple stable components on its surface. Cerium trifluoride is used as an intermediate layer to provide support, so that the elements of each layer are distributed in a gradient, thereby improving the bonding strength between the neodymium fluoride / dysprosium fluoride layer and the glass matrix. The cerium element penetrates into the glass matrix through thermal diffusion under a higher melting environment and acts as an intermediate layer. The higher melting temperature is conducive to the rapid penetration of the cerium element. The lower melting temperature in the latter stage is conducive to refining the grains, improving the density and uniformity of the glass container, improving the wear resistance of the glass container, and reducing the segregation phenomenon.

[0073] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a high-strength cosmetic glass container, characterized in that: The preparation method comprises the following steps: 1) Grinding and mixing quartz sand, soda ash, aluminum oxide, borax, barium carbonate, calcium oxide, magnesium oxide and cerium trifluoride raw materials to obtain a premix; 2) heating and melting the premix while continuously stirring to obtain a base liquid; 3) After adding neodymium fluoride and dysprosium fluoride to the base liquid, the temperature is lowered and melted to obtain glass liquid; 4) Injecting the molten glass into the preheated copper mold to form a preform; 5) heat treating the preform to obtain a high-strength cosmetic glass container; In step 2), the heating and melting is performed at a temperature of 1600-1700° C. for 35-45 minutes; In step 3), the temperature reduction melting is melting at a temperature of 1550-1640° C. for 15-20 minutes; In step 5), the heat treatment is annealing at a temperature of 480-520° C. for 5-6 hours, air cooling to a temperature of 420-460° C. for annealing for 1.0-1.5 hours, and heat treatment at a temperature of 630-650° C. for 2-3 hours.

2. The method for preparing a high-strength cosmetic glass container according to claim 1, characterized in that: In step 1), the grinding is grinding to a particle size of 0.6-0.8 mm.

3. The method for preparing a high-strength cosmetic glass container according to claim 1, characterized in that: In step 4), the copper mold is preheated to a temperature of 300°C.

4. The method for preparing a high-strength cosmetic glass container according to claim 1, characterized in that: The high-strength cosmetic glass container comprises the following components in parts by weight: 100-120 parts of quartz sand, 20-25 parts of soda ash, 10-12 parts of aluminum oxide, 6-8 parts of borax, 2.6-3.5 parts of barium carbonate, 12-16 parts of calcium oxide, 4-6 parts of magnesium oxide, 2.0-2.5 parts of cerium trifluoride, 1.5-2.0 parts of neodymium fluoride and 0.5-0.6 parts of dysprosium fluoride.

Citation Information

Patent Citations

  • Green and environment-friendly cosmetic glass bottle

    CN111333320A